The Correlation between Quality, Professionalism and Commitment with Teacher Performance - Hikmat (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2024)
This study aims to find out whether there is a relationship between these variables either separately or together. This research is classified as a correlational research consisting of three independent variables of teacher quality and professionalism, commitment and one variable of educator performance. with a sample of 40. The method used in this study is a survey method with a correlational approach, where data on the variables of teacher quality, professionalism and commitment are all collected with a questionnaire instrument using a rating scale. All instruments are tested by multiple linear regression tests. The results of the study show that there is a very significant positive relationship between the quality of teachers' work, commitment, and professionalism and the performance of education personnel. Based on the results of the research, it can be concluded that the performance of educators can be improved through quality, professionalism and commitment. Keywords: correlation study, quality, professionalism, commitment, performance of educators.